Developing and testing a mobile application for breastfeeding support: The Milky Way application. Issue 2 (March 2021) - Meedya, Shahla; Win, Khin; Yeatman, Heather; Fahy, Kathleen; Walton, Karen; Burgess, Lois; McGregor, Deborah; Shojaei, ParisaSadat; Wheatley, Eden; Halcomb, Elizabeth
Abstract: Background: Supporting women to continue breastfeeding is a global challenge. The Milky Way Program is an effective face to face intervention to increase breastfeeding rates up to six months postpartum. The sustainability and access to the Milky Way Program could be enhanced by transforming it into a mobile application allowing women to access relevant information from their own place at a convenient time. Aim: To explore the process of transforming the Milky Way Program into an acceptable and usable mobile health application. Method: Stakeholders including multidisciplinary researchers and end-users designed the application based on the Milky Way Program by using Persuasive System Design principles. A mixed-method approach was used in the development and evaluation process. Seven women were recruited through convenience sampling to pilot test the application. The women's feedback was collected through an online survey six weeks after birth and individual interviews at four months postpartum. Findings: Women in the pilot study reported that the breastfeeding application was well designed, easy to use, interactive, reassuring and evidence-based with credible sources of information. Conclusion: The Persuasive System Design model combined with end-user engagement can feasibly inform the development of an acceptable and usable mobile health application for breastfeeding based on a proven clinical intervention. Further rigorous testing is required to evaluate the effectiveness of the application on breastfeeding initiation and duration.